Avaliação da intenção de uso do Whatsapp, como ferramenta de ensino/aprendizagem, por professores do ensino superior - Santos, Leonardo Campinha dos (2018)
The use of WhatsApp has been studied as a tool and a new perspective to support teachers in the classroom environment. This work aimed to identify which variables influence the acceptance of WhatsApp by university professors, as a tool for the teaching / learning process. The use of WhatsApp in daily life and the performance in face-to-face teaching were important premises for the selection of respondents. The Davis Technology Acceptance Model (TAM) was used for its robustness to the proposed evaluation. Studies on the application of the TAM model to the acceptance of m-learning were important to compare the presented results. A questionnaire was applied online, which resulted in a sample of 229 teachers, which was analyzed using the Structural Equation Modeling (SEM). The results confirmed the validity of 6 of the 8 proposed hypotheses. The relation of the Perceived Use Ease on Utility, foreseen in the original model, was not confirmed. The Compatibility construct obtained great significance on Perceived Usability, Perceived Utility and Attitude in Relation to Use, demonstrating a perspective for future studies. The Attitude to Use was the factor that had the greatest influence on WhatsApp's Intention to Use. Finally, the results of this study suggest that university teachers consider the relevant aspects and influencers of a positive attitude towards the use of Whatsapp to be compatible with their values, needs and experiences, and the perception of how useful their use can be.